ESTIMASI JARAK GENETIK DAN FAKTOR PEUBAH PEMBEDA RUMPUN KELINCI MELALUI ANALISIS MORFOMETRIK - ukurta pinem (Jurnal Peternakan Integratif, 2014)
ABSTRACT The research aims to determine estimation of mahalanobis genetic distance. There was conducted in farmer groups Rehna Latersia Berastagi (North Sumatra). The objectives of this research using 227 heads rabbit of 20 strain rabbit, strain were analized Rex, English Spot (ES), English Angora (AI), Angora Francis (AF), Vlaamse Reus (VR), Lyon, Lop, Dwarfth, Lilo (Lyon x Lop), Loplylo (Local Lop x Lilo), Lyplyp (F1 Lilo) , Anglolylo (Local Angora x Lilo), Loes (Local x ES), Lela (Loes x lyang), Lorex (Local x Rex), Lovla (Local x VR), Lilolop (Lilo x Lop), Lyalya (F1 lyang), Angrexlya ((Angora x Rex) x lyang), and lyang (Lyon x Angora). Data were collected  consist of the head (length, width), ears (length, width), chest (girth, deep, wide), long bones (radius-ulna, humerus, tibia, femur, spine), wide hips, long hair (back, hips, head, between the ears , the head between the eyes , stomach). The results showed that the rabbit ES, VR, Lovla, and Loes have a larger body size, while AI and AF have longer hair than the other rabbit strains, fenogram tree formed four groups, the far genetic distance showed between VR rabbit by Dwarfth (8,24), ES by Dwarfth (8,28), the close genetic distance showed Loplylo by Lilo (1,31), and Loplylo by Lop (1.66). Results of canonical analysis showed that the most discriminant variables were obtained by fur length type on (abdomen, hips, between the eyes, back) for first canonical, and length (head of the humerus bone, and ear) for second canonical. The conclusion of this study is the rabbit with the same purpose showed relative high on mixture value, and have relative similar morphometrics. Keywords : Rabbit, Genetic Distance, Morphometrics